The Influence of Tax Education and Tax Centers on Taxpayer Literacy in Supporting Public Financial Management Accountability - Nugraha Abhull Azwad; Andi Indah Lestari; Shalzabila Shalzabila (CV Edujavare Publishing, 2026)
Taxes are the main source of state revenue which plays an important role in financing the development and implementation of public services. Therefore, increasing tax literacy is one of the strategic efforts in supporting accountability in public financial management. This study aims to analyze the influence of Tax Education and Tax Center on Taxpayer Literacy in supporting the accountability of public financial management in Makassar City. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to 100 taxpayers selected using the Simple Random Sampling technique. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The results of the study show that simultaneously Tax Education and Tax Center have a significant effect on Taxpayer Literacy. Partially, Tax Education has a positive and significant effect on Taxpayer Literacy, while Tax Centers have no significant effect. These findings show that the increase in people's tax literacy is more influenced by the tax education received than the existence of Tax Centers that have not been utilized optimally. The determination coefficient value of 43.7% showed that Tax Education and Tax Center were able to explain the variation in Taxpayer Literacy, while the rest was influenced by other factors outside the research model. This study concludes that Tax Education has an important role in improving people's tax literacy which can ultimately support strengthening the accountability of public financial management. Therefore, the government, the Directorate General of Taxes, and universities need to strengthen tax education programs and optimize the role of Tax Centers as a means of increasing public tax literacy.